Lovesick Ellie. 3 - Fujimomo (Kodansha USA Publishing, LLC, 2022)
"Plain Eriko Ichimura's love and fantasies grow in equal measure as she gets to know smooth-spoken, handsome Akira Ohmi's true bratty nature. What's more, after a rather intimate moment at the library, Ohmi tells her, 'Let's continue--after you pass your exam.' After receiving her 'prize' from Ohmi, Ellie finds her friend, Sara, unwittingly entrenched in school rumors--including one that claims Sara is secretly dating Ohmi?! "--Page [4] of cover.